THE INFLUENCE OF PRODUCT QUALITY AND BRAND TRUST ON THE DECISION TO PURCHASE WHEY PROTEIN EVOLENE PRODUCTS IN GYM MEMBERS IN GRESIK - Fernando Bryan Baki Mandonsa; Sri Andayani; Agung Pujianto (International Journal of Artificial Intelligence for Digital Marketing, 2024)
In contemporary times, a significant number of individuals possess knowledge on the significance of physical activity and have incorporated it into their everyday routines. This significantly influences the growth of the sports industry. Due to the rapid expansion of the sports industry, particularly in the fitness sector, there has been significant growth in the whey protein market. Individuals who engage in regular physical activity, particularly those who are members of fitness centres, require whey protein as a supplementary source of nutrition to fulfil their daily protein requirements. The whey protein sector presents a lucrative market opportunity for whey protein producers and companies, particularly Evolene. The objective of this study is to assess the impact of Product Quality (X1) and Brand Trust (X2) on the Purchasing Decisions (Y) of Evolene Whey Protein Products. This research is a quantitative study that focuses on the community of male consumers who use evolene whey protein in gyms in Gresik. 97 consumers at Surya Gym Members completed a survey using Google Form, providing feedback on their use of evolene whey protein. The research employed validity and reliability tests to assess the instruments. This study employed traditional assumption testing, including linearity tests, normalcy tests, and Multicollinearity tests. The analysis in this research employs statistical tests such as the t-test, F-test, and coefficient of determination test (R2), using the data analysis technique of multiple linear regression. The analysis of product quality and brand trust variables indicates that both variables, Product Quality and Brand Trust, have a positive and significant impact on the Purchasing Decision of Evolene Whey Protein Products for Gym Members in Gresik.